Fischer-Tropsch Synthesis in supercritical Co2 – Inhibition of Co2 selectivity for enhanced hydrocarbon production. (1st December 2017) - Benoit, Jeremiah; Perry, Derek; Mondal, Kanchan
Graphical abstract: Highlights: The use of supercritical CO2 as a solvent for FTS is discussed. Suppression of CH4 selectivity achieved. Suppression of CO2 formation achieved. Up to 10% CO2 conversion to hydrocarbons. Liquid product contains high oxygenates at low CO2 concentrations. Abstract: It has been generally observed that the fraction of the carbon in coal reporting as non methane hydrocarbons during coal to liquid (CTL) fuels process employing gasification and Fischer Tropsch Synthesis (FTS) using Fe based catalysts is less than 17% while theoretical limit for a CTL is around 52%. The use of supercritical CO2 as a solvent for FTS is shown to increase the reaction rates, suppress CO2 selectivity, reduce CH4 selectivity and thereby increase chain growth and improve the heat transfer and wax dissolution characteristics to increase catalyst longevity. This paper presents the results from proof of concept studies on FT synthesis in supercritical CO2 from syngas (H2 :CO ∼1:1) typically produced from coal gasification and using a Fe-Zn-K/γ-alumina catalyst. Experiments were conducted with syngas alone, syngas diluted with N2 and syngas diluted with CO2 . The high pressures improved the conversions and reduced the CO2 emissions. The dilution with N2 somewhat improved the CO conversions and CO2 emissions. However, CH4 emissions were found to increase. When diluted with CO2 and experiments conducted at pressures above the critical pressure, the data show, both, an overall shift in the product distribution towards higher hydrocarbons and reduction in the parasitic loss of carbon efficiency due to carbon dioxide formation along with significant improvement in the conversion rates. The use of the supercritical CO2 (ScCO2 ) inhibited methane and converted some of the CO2 .